Strategi Guru PPKn dalam Meningkatkan Profil Pelajar Pancasila dimensi Bernalar Kritis di SMP Muhammadiyah 4 Surakarta - Widayati, Oktaviani; Patmisari, Patmisari (Academy of Education Journal, 2024)
Education is the main provision to face the dynamics of life which continues to develop and experience change. The world of education is currently facing many very complex and diverse problems, starting from deficiencies in the learning process and learning evaluation. Education in the 21st century requires a shift in mindset in learning methods, where major emphasis is given to developing 21st century skills to empower students with relevant and competitive abilities. A learning approach is needed that is able to shift the focus of learning from teacher-centered to student-centered. The role of teachers is very important in supporting the development of students so that they acquire critical, innovative, creative and high moral attitudes which aim to form complete individuals. This research aims to determine the strategies of PPKn teachers in improving the Pancasila Student Profile in the critical reasoning dimension at SMP Muhammadiyah 4 Surakarta. This research was carried out for approximately 5 months. The method used in this research was descriptive qualitative where the researcher will describe based on data obtained from the field. Data sources were obtained from interviews with the Deputy Head of Curriculum, PPKn teachers, students, observations and documentation at school. Data collection techniques in this research used observation, interviews and documentation. The results of this research showed that the PPKn teacher's strategy in increasing the dimensions of critical reasoning is by using a variety of learning models or methods, the teacher's strategy is to get students to like reading or literacy, the second strategy is the teacher giving examples or actual events, the third strategy was the teacher giving HOTS questions, The fourth strategy was that students were able to solve problems through discussions, questions and answers and presentations and finally school facilities that support learning.